Collection and Reporting of Patient-reported Outcome Measures in Arthroplasty Registries: Multinational Survey and Recommendations. Issue 10 (October 2021) - Bohm, Eric R.; Kirby, Sarah; Trepman, Elly; Hallstrom, Brian R.; Rolfson, Ola; Wilkinson, J. Mark; Sayers, Adrian; Overgaard, Søren; Lyman, Stephen; Franklin, Patricia D.; Dunn, Jennifer; Denissen, Geke; et al.
Abstract: Background: Patient-reported outcome measures (PROMs) are validated questionnaires that are completed by patients. Arthroplasty registries vary in PROM collection and use. Current information about registry collection and use of PROMs is important to help improve methods of PROM data analysis, reporting, comparison, and use toward improving clinical practice. Questions/purposes: To characterize PROM collection and use by registries, we asked: (1) What is the current practice of PROM collection by arthroplasty registries that are current or former members of the International Society of Arthroplasty Registries, and are there sufficient similarities in PROM collection between registries to enable useful international comparisons that could inform the improvement of arthroplasty care? (2) How do registries differ in PROM administration and demographic, clinical, and comorbidity index variables collected for case-mix adjustment in data analysis and reporting? (3) What quality assurance methods are used for PROMs, and how are PROM results reported and used by registries? (4) What recommendations to arthroplasty registries may improve PROM reporting and facilitate international comparisons? Methods: An electronic survey was developed with questions about registry structure and collection, analysis, reporting, and use of PROM data and distributed to directors or senior administrators of 39 arthroplasty registries that were current or former members of the International Society of Arthroplasty Registries. In all, 64% (25 of 39) of registries responded and completed the survey. Missing responses from incomplete surveys were captured by contacting the registries, and up to three reminder emails were sent to nonresponding registries. Recommendations about PROM collection were drafted, revised, and approved by the International Society of Arthroplasty Registries PROMs Working Group members. Results: Of the 25 registries that completed the survey, 15 collected generic PROMs, most frequently the EuroQol-5 Dimension survey; 16 collected joint-specific PROMs, most frequently the Knee Injury and Osteoarthritis Outcome Score and Hip Disability and Osteoarthritis Outcome Score; and 11 registries collected a satisfaction item. Most registries administered PROM questionnaires within 3 months before and 1 year after surgery. All 16 registries that collected PROM data collected patient age, sex or gender, BMI, indication for the primary arthroplasty, reason for revision arthroplasty, and a comorbidity index, most often the American Society of Anesthesiologists classification. All 16 registries performed regular auditing and reporting of data quality, and most registries reported PROM results to hospitals and linked PROM data to other data sets such as hospital, medication, billing, and emergency care databases. Recommendations for transparent reporting of PROMs were grouped into four categories: demographic and clinical, survey administration, data analysis, and results. Conclusion: Although registries differed in PROM collection and use, there were sufficient similarities that may enable useful data comparisons. The International Society of Arthroplasty Registries PROMs Working Group recommendations identify issues that may be important to most registries such as the need to make decisions about survey times and collection methods, as well as how to select generic and joint-specific surveys, handle missing data and attrition, report data, and ensure representativeness of the sample. Clinical Relevance: By collecting PROMs, registries can provide patient-centered data to surgeons, hospitals, and national entities to improve arthroplasty care.